"Something feels like it's not coming back": the climate crisis: poetic awakening to what is at stake. Issue 1 (2nd January 2023) - Kingston, Breda
ABSTRACT: The gravity of the climate crisis, the damage attributable to the actions of humankind and the need for urgent action to avert catastrophe are all well established. Despite knowing these scientific facts, we continue to act as if we are not fully awake to the reality of the threat to all life on earth. In this piece of literary criticism, I will look at some of Jori Graham's poetry to explore how poetic transformation of the facts about the climate crisis could contribute to our awakening to what is at stake and how her work could facilitate conversation between us about the psychological impacts that we experience. I will also refer briefly to Denise Levertov's writing on the concept of irremediable damage to the earth.